Laparoscopic Roux-en-Y gastric bypass versus laparoscopic sleeve gastrectomy for 5-year hypertension remission in obese patients: a systematic review and meta-analysis. Issue 2 (February 2020) - Climent, Elisenda; Goday, Albert; Pedro-Botet, Juan; Solà, Ivan; Oliveras, Anna; Ramón, José Manuel; Flores-Le Roux, Juana Antonia; Checa, Miguel Ángel; Benaiges, David
Abstract : N/A: Controversial results exist on mid-term effects of Roux-en-Y gastric bypass and sleeve gastrectomy on hypertension remission. The aim of the present systematic review was to study 5-year hypertension remission after both procedures. One-year hypertension remission and SBP and DBP pressure change at 1 and 5 years after both surgical techniques were also evaluated. We searched MEDLINE, EMBASE and The Cochrane Central Register of Controlled Trials (CENTRAL). Thirty-two articles were included (six randomized controlled trials, 18 cohort and eight case–control studies). The proportion of patients with hypertension remission was greater for those treated with gastric bypass compared with sleeve gastrectomy at 5 years (RR = 1.26, 95% CI = 1.07–1.48) and 1 year (RR = 1.14, 95% CI = 1.06–1.21). Gastric bypass and sleeve gastrectomy did not differ in terms of SBP or DBP change. Patients treated with gastric bypass present a higher hypertension remission rate at 1 and 5 years.